Policy Implementation Strategies for Enhancing Community Participation in the Complete Systematic Land Registration Program: A Case Study of the Gowa Regency National Land Agency - Nur Fajriani S; Wafa Khairunisa (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the implementation strategy of the National Land Agency (BPN) in increasing community participation in the Complete Systematic Land Registration (PTSL) Program using Edward III's policy implementation model. A qualitative case study approach was employed through observation, interviews, and document analysis involving BPN officers, village PTSL implementers, and the community in Gowa Regency. The findings indicate that effective policy implementation is achieved through the synergy of communication, resources, disposition, and bureaucratic structure. These dimensions collectively strengthen public awareness, trust, and participation in land registration. The study enriches Edward III's implementation model by highlighting collaborative governance practices at the local level.